Exploring microRNA Signatures of DNA Damage Response Using an Innovative System of Genotoxic Stress in Medicago truncatula Seedlings - Gualtieri, Carla; Gianella, Maraeva; Pagano, Andrea; Cadeddu, Tiziano; Araújo, Susana; Balestrazzi, Alma; Macovei, Anca (Frontiers in Plant Science, 2021)
One of the challenges that living organisms face is to promptly respond to genotoxic stress to avoid DNA damage. To this purpose, all organisms, including plants, developed complex DNA damage response (DDR) mechanisms. These mechanisms are highly conserved among organisms and need to be finely regulated. In this scenario, microRNAs are emerging as active players, thus attracting the attention of the research community. The involvement of miRNAs in DDR has been investigated prominently in human cells whereas studies in plants are still scarce. To experimentally investigate the involvement of plant miRNAs in the regulation of DDR-associated pathways, an ad hoc system was developed, using the model legume Medicago truncatula. Specific treatments with camptothecin (CPT) and/or NSC120686 (NSC), targeting distinct components of DDR, namely topoisomerase I (TopI) and tyrosyl-DNA phosphodiesterase 1 (TDP1), were used. Phenotypic (germination percentage and speed, seedling growth) and molecular (cell death, DNA damage, gene expression profiles) analyses demonstrated that the imposed treatments impact DDR. Our results show that these treatments do not influence the germination process but rather inhibit seedling development, causing an increase in cell death and accumulation of DNA damage. Moreover, treatment-specific changes in the expression of SOG1 (Suppressor of gamma response 1), master-regulator of plant DDR, were observed. Additionally, the expression of multiple genes playing important roles in different DNA repair pathways and cell cycle regulation were differentially expressed in a treatment-specific manner. Subsequently, specific miRNAs identified from our previous bioinformatics approaches as putatively targeting genes involved in DDR processes were investigated alongside their targets. The obtained results indicate that under most conditions when a miRNA is upregulated the corresponding candidate target gene is downregulated, providing an indirect evidence of miRNAs action over these targets. Hence, the present study extends the present knowledge on the information available regarding the roles played by miRNAs in the post-transcriptional regulation of DDR in plants.